A rare case of pancreato-pleural fistula with left sided massive pleural effusion - V., Priyadharshini; S., Sanjay Surya G.; Shankar, Gowri A.; Dhande, Sachin K.; Pichaimuthu, Anbalagan (International Journal of Advances in Medicine, 2022)
Pancreaticopleural fistula is a very rare complication of acute and chronic pancreatitis. High index of suspicion is needed to diagnose in patients with alcohol induced pancreatitis, presenting with recurrent or persistent pleural effusion. Patient typically presented with pulmonary symptoms, rather than abdominal complaints, leading to delay in the diagnosis. Here we present a case of a known chronic pancreatitis who presented to us with massive left sided pleural effusion. Blood coloured pleural fluid analysis showed lipase and amylase levels in hundred thousand and ten thousand ranges. Diagnosis was made by CECT abdomen and confirmed with MRCP. Patient was treated with first line medical management of thoracocentesis and ERCP with pancreatic duct stenting.